KONSENTRASI INDUSTRI DAN RETURN SAHAM: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Eloi Ebenhazer Natalinov; Perminas Pangeran (Fakultas Bisnis UKDW, 2013)
The purpose of this study is to examine the effect of industry concentration to future stock return. We analyze all industries listed in Indonesia Stock Exchange over 2007 - 2009 period. By using regression analysis, the result shows that companies operating in less concentrated or more competitive industries generate higher future stock return. In another word, firms in more concentrated or less competitive earn lower future stock return. In addition, this study reveals that size has negative effect on future stock return, while leverage show not such effect. This result indicates that there is difference in the size of companies. Indonesian concentrated industries are dominated by the large compenies. Keywords: industries concentration, industries stock return, competitive industries